India Migration Report 2009 : past, present and the future outlook - India. Jawaharlal Nehru University. School of Social Sciences. International Migration and Diaspora Studies (IMDS) Project; Binod Khadria (New Delhi: JNU, 2009)
India Migration Report 2009 provides an overview of migration from India to the major destination countries as well as immigration to India. The focus of the report is to put together issues and concerns of significance in the contemporary contexts of migration - both continuing and emerging - and bring out a systematic, regular and futuristic source of information and analysis on international mobility of people in India.
Chapter 1. India as a major emigration country : an overview of trends and characteristics -- Chapter 2. Immigrants in India : an overview -- Chapter 3. The migration cycle -- Chapter 4. Continuing and emerging concerns -- Chapter 5. Perspectives on mobility of health professionals -- Chapter 6. Policy perspectives on international migration -- Chapter 7. Future outlook -- Bibliography.
Keywords: India -- Emigration and immigration; Emigration and immigration; India